2011
DOI: 10.1074/jbc.m111.294843
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Xcp Pseudomonas aeruginosa Type II Secretion Machinery through Multiple Interactions with Substrates

Abstract: Background:The type II secretion machinery secretes large toxins across the bacterial envelope. Results: We identified multiple interactions between secreted exoproteins and components of the machinery. Conclusion: We propose a model for substrate recognition and transport during the secretion process. Significance: Our data shed light on the operating mode of the type II secretion pathway and provide new potential targets for drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 31 publications
4
122
0
Order By: Relevance
“…Here it is suggested that the exotoxin sitting on the grown pseudopilus induces conformational changes in the secretin, which results in the opening of the periplasmic gate and the final release of the toxin (37,57). If a pseudopilus triggers opening of the Thermus PilQ complex, thereby enabling DNA uptake, a direct interaction of the pseudopilus structures and the PilQ complex is a prerequisite.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Here it is suggested that the exotoxin sitting on the grown pseudopilus induces conformational changes in the secretin, which results in the opening of the periplasmic gate and the final release of the toxin (37,57). If a pseudopilus triggers opening of the Thermus PilQ complex, thereby enabling DNA uptake, a direct interaction of the pseudopilus structures and the PilQ complex is a prerequisite.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…7). This result was perhaps not surprising given the numerous studies that have demonstrated several different points of interaction between GspC and GspD (45)(46)(47)(48); as a result, coexpression of ExeC with ExeD would more closely resemble a wild-type situation than expression of ExeD alone. The necessity for additional, highly conserved assembly factors, such as the Bam complex, has not been determined in A. hydrophila, although Bam-independent assembly of the T2SS secretin has been shown for other bacteria (49,50).…”
Section: Discussionmentioning
confidence: 81%
“…In this case, the exoprotein could adopt a secretion-competent conformation prior to secretion and another conformation once released in the extracellular medium [138]. This sequence of events is probably not the case with P. aeruginosa and V. cholerae T2SSs for which interactions found between substrates and secreton components were detected using purified secreted proteins [41,61,70]. Obviously the question of specific substrate recognition is far from being resolved.…”
Section: Substrate Recognition and Transport By The T2ss Machinementioning
confidence: 99%
“…However, the replacement of the intermediary domain between TM and HR called TM/HR (figure 4) leads to secretion defect, suggesting that this domain plays an essential role in specificity and potentially in substrate recognition. Recently, a set of in vitro experiments has revealed direct interactions between purified XcpP C and two substrates of the Xcp T2SS, the elastase (LasB) and the lipase (LipA) [70]. Importantly, no interaction was detected using the substrate of the second P. aeruginosa T2SS (Hxc), i.e.…”
Section: The Outer Membrane Secretinmentioning
confidence: 99%